Democratic values, relative deprivation, political trust, and the resilience of corruption in Portugal: a survey analysis - Clemente, Felippe (Crime, law and social change, 2024)
Corruption is commonly defined as deviant behaviour that strays from established legal and formal norms, as well as expected conduct when fulfilling official duties and responsibilities. It is essential to stress that the acceptance or condemnation of such behaviour hinges primarily on how well evaluators comprehend these standards. This implies that citizens’ assessments of the impact of corruption on their lives and society are heavily influenced by the values they hold dear within a democracy and their trust in democratic institutions to uphold and safeguard those values. Based on recently collected survey data, we demonstrate that citizens’ adherence to process-oriented democratic values, their feeling of relative deprivation and their level of political trust significantly affect their egocentric perceptions of the effects of corruption and tolerance towards corruption. Furthermore, we find that control variables, such as self-reported experiences of corruption, age, education, income, and exposure to social media, also exert a significant influence on our dependent variables. By linking citizens’ egocentric perceived corruption effects and intolerance towards corruption with their procedural notion of democracy, feeling of relative deprivation and political trust, this study contributes to the understanding of the resilience of this intricate phenomenon in democratic societies.